Collaborative care for depression and suicide prevention: a feasible intervention within the Mexican health system - Sol Durand-Arias; Gloria Cordoba; Guilherme Borges; Eduardo Á. Madrigal-de León (Instituto Nacional de Salud Pública, 2021)
Mexico faces an enormous challenge in attending mental health disorders with depression rising as one of the five main contributors to disability adjusted life years (DALYs) and increasing suicide rates. These challenges are coupled with a dearth of resources and an inefficient allocation of the meager funds. While no magical bullet is available to ameliorate this situation in the short term, here we discuss current concepts and experiences that could be used in Mexico to deliver better primary mental health care. We focus on depression and suicidal behavior and argue that collaborative care is a feasible and replicable model, emphasizing the importance of training non-specialized primary care personnel to become case managers and provide primary mental health care. Mexico is currently undergoing a process of changes, including the emergence of universal health care. The time seems right to make mental health care more transversal, widely available and scientifically proven.